2022
DOI: 10.1002/ceat.202200025
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Quercetin in a Mixed Nanomicellar System to Enhance its Cytotoxicity against Breast Cancer Cells

Abstract: The therapeutic potential of quercetin-loaded Pluronic F-127 (PF-127)/Tween 80 mixed nanomicelles as a passive targeted drug delivery system for breast cancer therapy is evaluated. Quercetin-loaded mixed nanomicelles with different mass ratios of drug/PF-127/Tween 80 were prepared by thin-film hydration method. The physical interactions of quercetin with PF-127 and Tween 80 in an optimal ratio were investigated. The results of in vitro drug release experiments showed that the mixed micellar system exhibits a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…However, after 72 h, there was a maximum cumulative release of only 7% in acidic pH, indicating a much lower bioavailability than what we measured (65% at 72 h). Li and team [ 74 ] have reported on a pegylated nanoliposomal system with 8.5% drug loading that displayed a sustained release pattern with a much more favorable maximum release, while the similar sustained and maximum cumulative release was recorded by Davarnejad and co-workers [ 75 ] who used mixed nanomicelles with a relatively low drug loading of 2.3%. However, these systems were tested at pH 7.4, modeling the release in normal physiological pH, but no information can be extrapolated about the release in the characteristically acidic pH of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 80%
“…However, after 72 h, there was a maximum cumulative release of only 7% in acidic pH, indicating a much lower bioavailability than what we measured (65% at 72 h). Li and team [ 74 ] have reported on a pegylated nanoliposomal system with 8.5% drug loading that displayed a sustained release pattern with a much more favorable maximum release, while the similar sustained and maximum cumulative release was recorded by Davarnejad and co-workers [ 75 ] who used mixed nanomicelles with a relatively low drug loading of 2.3%. However, these systems were tested at pH 7.4, modeling the release in normal physiological pH, but no information can be extrapolated about the release in the characteristically acidic pH of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 80%
“…The outcomes of drug release experiments conducted in a laboratory indicated that the mixed micellar system demonstrates a more extended and consistent release pattern when compared to the free quercetin solution. Besides, it exhibited a lower half‐maximal IC50 than the free drug 107 …”
Section: Advancements In Natural Substance Enhancement Through Nanote...mentioning
confidence: 99%
“…Besides, it exhibited a lower half-maximal IC50 than the free drug. 107 Nanoparticles can take a role in improving the administration of quercetin by enhancing its uptake within cancer cells. Nanocarriers can be engineered with surface modifications that facilitate specific interactions with cancer cell receptors, promoting efficient uptake of quercetin.…”
Section: Quercetinmentioning
confidence: 99%